Coherent phase control in e-Ar scattering in a bichromatic laser field in the second born approximation - Zhou, Bin; Li, Shu-Min (Chinese physics letters, 2010)
We study the elastic scattering of atomic argon by an electron in the presence of a bichromatic laser field in the second Born approximation. The target atom is approximated by a simple screening potential. We explore the dependences of the differential cross sections on the relative phase ϕ between the two components of the radiation field and discuss the influence of the number of photons exchanged on the phase-dependence effect. Moreover, for different scattering angles and incident electron energies, the differential cross sections are notably different.